2023
DOI: 10.31234/osf.io/9d34r
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Do We Need Metacognition for Creativity? A Necessary Condition Analysis of Creative Metacognition

Abstract: Recent studies suggest that metacognitive knowledge and accurate metacognitive monitoring are associated with higher creativity. However, previous findings were based solely on traditional statistical analyses applying sufficiency causal logic. Necessary condition analysis (NCA) is a novel methodological approach that tests whether a given predictor represents a necessary condition that allows an outcome to exist. Employing NCA, the present study examines whether accurate metacognitive monitoring is a necessar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…According toMumford et al (1991), it is metacognitive monitoring that guides the overall creative problem-solving process.The role of metacognitive monitoring in divergent thinking tasks was examined by several studies(Rominger et al, 2022;. The accuracy of metacognitive monitoring was positively associated with creative performance(Pesout & Nietfeld, 2021) andUrban & Urban (2023, February 9) showed that highly creative individuals who are at the same time metacognitively inaccurate do not exist. Moreover, previous research suggests that more metacognitive skills are exhibited during creative performance, especially during performance in the most complex creativity tasks (such as Product Improvement Task;Preiss et al, 2019; Sanz de Acedo Lizarraga & Sanz de Acedo Baquedano, 2013;…”
mentioning
confidence: 99%
“…According toMumford et al (1991), it is metacognitive monitoring that guides the overall creative problem-solving process.The role of metacognitive monitoring in divergent thinking tasks was examined by several studies(Rominger et al, 2022;. The accuracy of metacognitive monitoring was positively associated with creative performance(Pesout & Nietfeld, 2021) andUrban & Urban (2023, February 9) showed that highly creative individuals who are at the same time metacognitively inaccurate do not exist. Moreover, previous research suggests that more metacognitive skills are exhibited during creative performance, especially during performance in the most complex creativity tasks (such as Product Improvement Task;Preiss et al, 2019; Sanz de Acedo Lizarraga & Sanz de Acedo Baquedano, 2013;…”
mentioning
confidence: 99%